Probiotic frozen yogurt containing high protein and calcium - M.S. Forbes; I.J. Jeon; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 1996)
A new frozen yogurt manufacturing procedure that is easily adaptable to the current practices of the frozen yogurt industry has been developed with probiotic culture and ultrafiltrated milk. The ultrafiltrated milk was heated to 185 degrees F for 35 min to obtain a desirable gel structure when fermented with the traditional yogurt culture of Streptococcus thermophilus and Lactobacillus bulgaricus. Probiotic cultures (Bifidobacterium and Lactobacillus spp.) were added to the yogurt mix just before freezing. The yogurt mix was frozen to an 85% overrun and hardened at -20 degrees F. The frozen product contained viable culture organisms at greater than or equal to 107 cells per gram and was stable for 6 mo. The frozen yogurt also contained twice the amount of protein, three times as much calcium, and nearly one-third less lactose than similar commercial products. The new product had excellent flavor, body, texture, and overall quality.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Frozen yogurt; Ultrafiltrated milk; Probiotic bacteria